Analisis Potensi Ekonomi dan Sektor Unggulan Kabupaten/Kota di Provinsi Kalimantan Timur - Tina Juniarta; Rifki Khoirudin; Suripto Suripto (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2023)
Regional economic growth and development are driven by the potential that not only influences one specific area but also has an impact on neighboring regions. One of the significant factors influencing regional economic growth and development is the dominant sector. To achieve the objectives of regional economic growth and development, a region must possess the potential and dominant sectors that contribute to economic improvement. The aim of this research is to identify the economic potential and dominant sectors influencing the economic growth of districts/cities in East Kalimantan Province. This study employs a quantitative approach with a descriptive research nature, utilizing data analysis techniques including Location Quotient and Shift-share analysis. Secondary data published by the Central Statistics Agency (BPS) of districts/cities in East Kalimantan Province for the years 2017-2020 were used. Based on the Location Quotient analysis results, two dominant sectors were identified in Paser District, seven in Kutai Barat District, three in Kutai Kartanegara District, one in Kutai Timur District, eight in Berau District, nine in Penajam Paser Utara District, thirteen in Mahakam Ulu District, twelve in Balikpapan City, fourteen in Samarinda City, and four in Bontang City. These dominant sectors play a pivotal role in driving economic growth in their respective regions, ultimately leading to increased economic prosperity.